Influence of kinesiological means on the motor fitness of 15-16 years-old skiers-racers - Golovko, D. E.; Zagrevskaya, A. I.; Shilko, T. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the effect of kinesiological means on the motor fitness of 15-16-year-old ski racers.